PEMBENTUKAN REMAJA ISLAM MASJID (RISMA) JANNATU ADNIN SEBAGAI WADAH DAKWAH DAN PENGEMBANGAN PEMUDA DI KELURAHAN PANORAMA KOTA - Japaruddin; Jefri Trianda Saputra; Nur Iliyin Fatimah; Siti Meutia Salma; Elsa Tri Wulan Ningrum; Dinda Suci (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study aims to describe the process of establishing the Remaja Islam Masjid (RISMA) Jannatu Adnin on Jalan Gandaria 7 No. 15, Panorama Village, Singaran Pati District, Bengkulu City, as an effort to develop youth potential based on mosque activities. This activity was carried out within the framework of the Research-Based Independent Learning Independent Campus Community Service Program (KKN MBKM), involving students from various study programs at the Faculty of Ushuluddin, Adab, and Dakwah. The research employed a descriptive qualitative method with a participatory approach through Focus Group Discussion (FGD), field observations, and in-depth interviews with mosque administrators and community leaders. The findings indicate that the establishment of RISMA Jannatu Adnin was implemented through four main stages: mapping youth potential, socialization and member recruitment, structuring the organizational board, and formulating the Articles of Association and Bylaws (AD/RT). These four stages successfully established a mosque-based youth organization with a clear institutional structure and organizational guidelines. Consequently, RISMA Jannatu Adnin can function as a forum for religious development, leadership cultivation, and the enhancement of youth participation and creativity in mosque-related activities.